Laser, radiofrequency, and ethanol ablation for the management of thyroid nodules. Issue 5 (October 2016) - Papini, Enrico; Gugliemi, Rinaldo; Pacella, Claudio Maurizio
Abstract : Purpose of review: The majority of benign thyroid nodules are nearly asymptomatic, remain stable in size, and do not require treatment. However, a minority of patients with growing nodules may complain of local symptoms or have cosmetic concerns, and thus seek surgical consultation. Recent findings: The timely use of ultrasound-guided minimally invasive procedures can change the natural history of benign enlarging thyroid nodules. The procedures produce persistent shrinkage of thyroid nodules and are associated with improvement of local symptoms. Among the various procedures, percutaneous ethanol injection represents the first-line treatment for relapsing thyroid cysts. In solid nonfunctioning nodules, laser and radiofrequency ablation produces a more than 50% reduction in nodular volume that remains persistent over several years. For hyperfunctioning nodules, thermal ablation techniques are not appropriate unless radioactive iodine is contraindicated or not accessible. Summary: MITs are best suited for the management of medium or large-sized nodules that are sonographically well visualized. Conversely, large nodules or nodular goiters that extend into the chest are difficult to treat. MITs are performed in outpatient clinics, are less expensive, and have a lower risk of complications, compared to surgery, and usually do not induce thyroid dysfunction. However, malignancy should be ruled out with a dedicated ultrasound neck assessment and repeat fine needle aspiration of the lesion before treatment.